Conservation of sex chromosomes in lacertid lizards - Rovatsos, Michail; Vukić, Jasna; Altmanová, Marie; Johnson Pokorná, Martina; Moravec, Jiří; Kratochvíl, Lukáš (Molecular ecology, 2016)
Sex chromosomes are believed to be stable in endotherms, but young and evolutionary unstable in most ectothermic vertebrates. Within lacertids, the widely radiated lizard group, sex chromosomes have been reported to vary in morphology and heterochromatinization, which may suggest turnovers during the evolution of the group. We compared the partial gene content of the Z-specific part of sex chromosomes across major lineages of lacertids and discovered a strong evolutionary stability of sex chromosomes. We can conclude that the common ancestor of lacertids, living around 70 million years ago (Mya), already had the same highly differentiated sex chromosomes. Molecular data demonstrating an evolutionary conservation of sex chromosomes have also been documented for iguanas and caenophidian snakes. It seems that differences in the evolutionary conservation of sex chromosomes in vertebrates do not reflect the distinction between endotherms and ectotherms, but rather between amniotes and anamniotes, or generally, the differences in the life history of particular lineages.
Keywords: Gene Dosage; Sex Chromosomes; Male; pohlavní chromozomy; konzervovaná sekvence; Conserved Sequence; genová dávka; biologická evoluce; mužské pohlaví; Lizards; ještěři; reptiles; Animals; sex chromosomes; ženské pohlaví; Biological Evolution; zvířata; molecular sexing; lizards; Female